ปัจจัยที่มีอิทธิพลต่อการก่ออาชญากรรมทางเพศของเยาวชนชายในกรุงเทพมหานคร - จามร สุนทรกิจ (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The objective of this research is to study factors influential in sexual crime committed by male youth in Bangkok Metropolis. Anthropological approach and researching technique such as in-depth interview, participant observation and field notes are used in data collection from 12 appropriately chosen subjects. The result of this research may be summarized as follows: The subject average age when committing crimes is 15.8 years old. Their present average age is 17.2 years old. 91.66% of them are Buddists. 24.99 % live in Bangkok. 41.66% of the offenders are charged with abducting of juvenile. 50 % of the subjects are pupils. 50 % out of which finish elementary education at the highest level. 58.33 % of them attend no school during the period of crime committing. The hypothesis test shows that the factors influential in sexual crime committed by male youth juvenile in Bangkok Metropolis include the subjects inadequate ecucation, weak family tie, being induced by friends, drug addiction, environment inappropriate for youth, and sexual provocation. However, low-income of families has no influence on the male youth juvenile delinquents.